Today and Future of Age-Related Macular Degeneration. (4th April 2012) - Liu, Kang; Xie, Bolin
Abstract : Age-related macular degeneration (AMD) is the leading cause of blindness in people over 50 in developed countries. Understanding of the pathologic process, genetic mechanisms, and risk factors of this disease has the benefit of seeking newer and more effective treatment options. Current clinical therapy for AMD shows a dramatic change from a decade ago. Anti-VEGF drug therapy is regarded as the more effective treatment for neovascular AMD now, especially combining PDT therapy. In the future, the genetic and biochemical therapies may be the promising treatments for AMD. This paper will focus on the progress of pathology, candidate genes of AMD, risk factors, and the existing drugs or surgical therapies available, in order to present some new directions of care with the prospect of improved vision in many patients suffered from AMD.